Composite rubber material for track rubber coating and preparation method thereof

By using carbon black doped modified boron nitride reinforcement filler and porous skeleton main filler in rubber materials, the filler composite system is formed, which solves the problem of insufficient wear resistance and aging resistance of existing rubber materials, and significantly improves the performance and service life of the material.

CN119751993APending Publication Date: 2025-04-04济南鲁联集团橡胶制品有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510049154.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The wear resistance and aging resistance of existing rubber materials are poor, limiting their performance and service life.

Method used

Carbon black doped modified boron nitride reinforcement filler and porous skeleton main filler are used to form a filler composite system through vacuum impregnation method, which is uniformly dispersed inside the rubber matrix to form a more complete filler network.

Benefits of technology

It significantly enhances the wear resistance, aging resistance and mechanical properties of rubber materials, and extends the service life of rubber materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751993A_ABST
    Figure CN119751993A_ABST
Patent Text Reader

Abstract

The invention discloses a composite rubber material for track rubber coating and a preparation method thereof, and relates to the technical field of polymer materials; the composite rubber material for track rubber coating consists of a carbon black-doped modified boron nitride reinforcing filler, a porous skeleton main filler, glutaric acid, natural rubber, styrene-butadiene rubber, benzothiazole disulfide and zinc oxide; the porous skeleton main filler consists of a modified melamine skeleton material, and multi-walled carbon nanotubes double-modified with stearic acid and chitosan; the carbon black-doped modified boron nitride reinforcing filler is attached to the skeleton structure of the porous skeleton main filler to form a filler compound system, which can be evenly dispersed in the rubber matrix to form a more complete filler network, and the network structure can enable the various components of the filler to better play a synergistic reinforcing role, and under the dual effects of the structure and the components, the wear resistance, aging resistance and mechanical properties of the rubber material are effectively enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and specifically refers to a composite rubber material for track rubber coating and a preparation method thereof. Background Art

[0002] Tanks and other heavy armored vehicles were initially designed with steel tracks, but sometimes they needed to travel on roads for transfers. In order to reduce damage to the road surface, rubber materials began to be used in conjunction with steel tracks, which were called rubber tracks. Compared with steel tracks, this type of rubber track is characterized by being light. The significant weight reduction not only makes the tracked vehicle faster and more accelerated, but also reduces fuel consumption and increases the cruising range. In terms of reducing noise, rubber tracks can effectively reduce noise based on the elasticity and deformation ability of rubber materials, and rubber tracks have better corrosion resistance when working in acid, alkali, and salt environments. However, since rubber tracks are usually formed in one piece, it is impossible to repair them like steel tracks by replacing damaged track plates at a fixed point. Instead, once a break occurs, the entire track must be replaced. Therefore, in order to adapt to more severe use environments, further research and development must be carried out in terms of material strength and durability.

[0003] The existing technology currently has the following problems:

[0004] The wear resistance and aging resistance of rubber materials are poor, which greatly limits the performance and service life of rubber materials. Summary of the invention

[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention proposes a composite rubber material for track coating, comprising the following components in parts by weight: 40-50 parts of carbon black doped modified boron nitride reinforcing filler, 20-25 parts of porous skeleton main filler, 8-10 parts of glutaric acid, 15-20 parts of natural rubber, 15-20 parts of styrene-butadiene rubber, 1-3 parts of benzothiazole disulfide, and 5-8 parts of zinc oxide.

[0006] The carbon black doped modified boron nitride reinforcing filler comprises the following components in parts by weight: 8-10 parts of modified boron nitride and 50-100 parts of carbon black.

[0007] The porous skeleton main filler comprises the following components in parts by weight: 10-20 parts of modified melamine skeleton material and 40-60 parts of multi-walled carbon nanotubes double-modified with stearic acid and chitosan.

[0008] The preparation method of the carbon black doped modified boron nitride reinforcing filler specifically comprises the following steps:

[0009] (1) Add 8.0-10.0g of boron nitride to 100mL of a sodium hydroxide solution with a mass fraction of 20-30%, heat and stir in an oil bath at 70-80℃ for 48h, wash with distilled water until neutral, and then vacuum dry. Hydroxylation treatment can improve the dispersibility and stability of boron nitride in aqueous solution, provide reaction sites for boron nitride, make it easier to carry out functional modification, and improve the interfacial affinity of boron nitride in polymer composite materials, so as to better play the role of boron nitride in enhancing the hardness of rubber materials, improving wear resistance and improving anti-aging performance, thereby obtaining hydroxylated boron nitride;

[0010] (2) Add 1-2 mL of γ-glycidyloxypropyltrimethoxysilane to 100 mL of 90% ethanol solution, stir for 0.5-1 h, then add the hydroxylated boron nitride described in step (1), heat in a water bath at 70-80° C. for 1 h, filter, wash the product with anhydrous ethanol for 3-5 times, and vacuum dry. γ-glycidyloxypropyltrimethoxysilane is used as a silane coupling agent to modify the filler, thereby improving the dispersibility of the hydroxylated boron nitride in the rubber matrix and enhancing the interaction between the rubber matrix and the hydroxylated boron nitride, which plays a positive role in improving the various properties of the rubber material, thereby obtaining modified boron nitride;

[0011] (3) Add the modified boron nitride described in step (2) to 2L of deionized water, perform ultrasonic treatment for 10-30 minutes to make it evenly dispersed, then add 50.0-100.0g of carbon black particles to the modified boron nitride dispersion, first perform high-pressure homogenization for 2-3 minutes, then perform high-speed shearing for 5-10 minutes, then perform ultrasonic treatment for 30-50 minutes, and finally perform high-pressure homogenization for 50-60 minutes, filter, wash the product with deionized water 3-5 times, and vacuum dry. Through this process, the carbon black particles are adsorbed and doped on the modified boron nitride sheet structure, which hinders the stacking of the boron nitride sheet structure and further improves the compatibility with the rubber matrix. At the same time, the load-bearing effect of the modified boron nitride also improves the aggregation of carbon black particles, which is conducive to a more complete physical combination of carbon black with rubber molecules, increasing its hardness and strength, improving wear resistance, oxidation resistance and weather resistance, preventing aging and deterioration, and effectively extending the service life of the rubber material, thereby obtaining a carbon black-doped modified boron nitride reinforcing filler;

[0012] Preferably, in step (3), the carbon black type is BC2110, which has finer particles, larger specific surface area, better reinforcement, and better processing performance.

[0013] The present invention also provides a method for preparing a composite rubber material for track rubber coating, which specifically comprises the following steps:

[0014] S1. Cut melamine into 4cm×4cm×0.5cm, wash it ultrasonically with 80% ethanol solution, dry it for later use, dissolve 0.3-0.5g tris(hydroxymethylaminomethane) in 250mL deionized water, and adjust the pH to 8.5 with hydrochloric acid solution, then put the pretreated melamine into tris(hydroxymethylaminomethane) buffer solution, add 0.2-0.5g dopamine, react at room temperature for 6-8h, collect the product after washing, melamine is a material similar to "elastic foam", its porous structure and high specific surface area characteristics, as a support structure of filler, give the rubber material excellent compression and cycle durability, can maintain stable performance under high pressure, and dopamine adheres to the melamine skeleton after polymerization, making the skeleton surface rough, which provides favorable conditions for building a more complex filler network, and obtains a modified melamine skeleton material;

[0015] S2, dissolving 0.8-1.0g chitosan in 200mL dilute acetic acid solution, stirring for 8-12h, standby, weighing 0.2-0.5g multi-walled carbon nanotubes and dispersing them in 20mL deionized water, ultrasonicating for 20-30min, and then slowly adding them to the chitosan solution, under condensation reflux conditions, magnetically stirring the mixed solution at 90-98°C for 5-6h, cooling to room temperature, adjusting the pH of the solution to 10.0 with dilute ammonia water, then adding 1-2mL glutaraldehyde, magnetically stirring at 50-60°C for 2-3h, washing the product with dilute acetic acid and deionized water in turn, centrifuging, freeze-drying, using glutaraldehyde as a cross-linking agent, and using a surface deposition cross-linking method to adsorb and wrap chitosan on the surface of multi-walled carbon nanotubes, which is not only conducive to the next step of modification treatment, but also can play the toughening effect of chitosan, so that the rubber material can better disperse stress when subjected to external force, reduce the generation and expansion of cracks, and obtain chitosan-modified multi-walled carbon nanotubes;

[0016] S3, dispersing the chitosan-modified multi-walled carbon nanotubes described in step S2 in 20 mL of deionized water, ultrasonicating for 20-30 min, dissolving stearic acid and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride in a mixture of 28 mL of acetone and 12 mL of anhydrous ethanol, and then adding the mixture to the chitosan-modified multi-walled carbon nanotube dispersion, magnetically stirring at 50-60° C. for 12-24 h, washing the product with anhydrous ethanol and deionized water in turn, centrifuging, and vacuum drying, and further grafting stearic acid on the surface of the chitosan-modified multi-walled carbon nanotubes with a water-soluble coupling agent 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride to modify the surface of the chitosan-modified multi-walled carbon nanotubes. After chitosan deposition and stearic acid grafting, the dispersibility of the multi-walled carbon nanotubes is improved, and the tube wall structure becomes rough, which is conducive to enhancing the adhesion ability, thereby obtaining stearic acid and chitosan dual-modified multi-walled carbon nanotubes;

[0017] S4, dispersing the multi-walled carbon nanotubes double-modified with stearic acid and chitosan described in step S3 in 100 mL of deionized water, then soaking the modified melamine skeleton material described in step S1 therein, taking it out, vacuum drying, and then repeating this process 1-3 times, the multi-walled carbon nanotubes double-modified with stearic acid and chitosan can be attached to the skeleton structure of the modified melamine skeleton material, forming a three-dimensional network filler, reducing the aggregation and entanglement of the filler, and can be evenly dispersed in the rubber matrix, better improving the wear resistance, aging resistance and mechanical properties of the rubber material, and obtaining a porous skeleton main filler;

[0018] S5. Disperse the carbon black doped modified boron nitride reinforcing filler in 100 mL of deionized water, infiltrate the porous skeleton main filler described in step S4 therein, take it out, vacuum dry it, and repeat this process 1-3 times to obtain a filler compound system. The carbon black doped modified boron nitride reinforcing filler is attached to the structure of the porous skeleton main filler by vacuum infiltration, which can give full play to the synergistic effect of the main material and the supplementary material, and the two form a unique network structure, which makes the filler network inside the rubber matrix more perfect and significantly enhances the dispersibility. and compatibility, mixing natural rubber and styrene-butadiene rubber in an internal mixer for 1-2 minutes at a temperature of 125-135°C and a rotation speed of 60-80rpm, and then adding a filler compound system, glutaric acid, benzothiazole disulfide and zinc oxide, wherein glutaric acid can also increase the crosslinking density between materials, thereby improving the ability of the rubber macromolecular chains to resist deformation, mixing for 20-30 minutes, mixing evenly, and then thinning and sheeting. After standing for 8 hours, a flat vulcanizer is used for compression molding to obtain a composite rubber material for track rubber coating;

[0019] Preferably, in step S2, the multi-walled carbon nanotubes are carboxylated multi-walled carbon nanotubes with a diameter of 10-20 nm and a length of 10-12 μm, which have high chemical activity, better mechanical properties and thermal stability, and are not easy to entangle and aggregate, and can significantly enhance the wear resistance, tear resistance and aging resistance of the rubber material, so that it exhibits better durability in harsh environments;

[0020] Preferably, in step S3, the amount of stearic acid added is 0.2-0.3 g, and the amount of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride added is 0.6-0.8 g, wherein stearic acid can not only promote the vulcanization reaction with zinc oxide, but also help promote the uniform dispersion of fillers such as carbon black in the rubber matrix, thereby improving the uniformity and stability of the rubber material.

[0021] The beneficial effects achieved by the present invention are as follows:

[0022] The present invention forms a filler compound system by attaching the carbon black doped modified boron nitride reinforcing filler to the skeleton structure of the porous skeleton main filler, which can be evenly dispersed in the rubber matrix to form a more complete filler network. This network structure can enable the various components of the filler to better play a synergistic reinforcing role. Under the dual effects of structure and components, the wear resistance, aging resistance and mechanical properties of the rubber material are effectively enhanced, and the service life of the rubber material is significantly extended; in the carbon black doped modified boron nitride reinforcing filler, the modified boron nitride is used as a carrier, and the high-strength and high-wear-resistant carbon black particles are adsorbed and doped in its flakes. In terms of layer structure, the interaction and stacking between the layers are reduced, and the compatibility with the rubber matrix is ​​improved. At the same time, the role of the carrier is also conducive to the uniform dispersion of carbon black particles, and it is more helpful to enhance the tensile strength, tear strength and wear resistance of the rubber material. Among them, carbon black has the ability to absorb ultraviolet rays, which can reduce the damage of ultraviolet rays to rubber. Boron nitride has good thermal conductivity and can reduce the aging of rubber caused by overheating. Therefore, carbon black and boron nitride work together to resist the erosion of rubber by external factors such as light and heat, thereby improving the aging resistance. In the porous skeleton main filler, dopamine is first polymerized and then adhered to a similar The melamine skeleton of the "elastic foam" is used to enhance the surface roughness, and then the multi-walled carbon nanotubes double-modified with stearic acid and chitosan are infiltrated and attached to the modified melamine skeleton material to form a three-dimensional network filler, which effectively reduces the aggregation and entanglement of the filler and improves the dispersion and compatibility in the rubber matrix. Among them, melamine can promote the cross-linking reaction of rubber, enhance the network structure and cohesion of rubber molecules, improve mechanical properties, wear resistance and stability, thereby reducing the wear and aging of rubber materials. After chitosan deposition and stearic acid grafting, the wall structure of the multi-walled carbon nanotubes becomes rough. The invention is beneficial to improving the stability and firmness of adhesion to the modified melamine skeleton material, and improving the dispersibility of the multi-walled carbon nanotubes. The chitosan, stearic acid and multi-walled nanotubes can also be combined to improve the wear resistance, aging resistance, tensile strength and tear strength of the rubber. The composite rubber material for track rubber coating is prepared by using carbon black doped modified boron nitride reinforcing filler, porous skeleton main filler, glutaric acid, natural rubber, styrene-butadiene rubber, benzothiazole disulfide and zinc oxide. The composite rubber material has excellent wear resistance, aging resistance and mechanical properties, and significantly prolongs the service life of the rubber material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope image of the brittle fracture surface of the composite rubber material for track rubber coating prepared in Example 1 of the present invention;

[0024] Figure 2 The mechanical properties of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0025] Figure 3The figures are the results of wear of Examples 1-4 and Comparative Examples 1-3 of the present invention;

[0026] Figure 4 This is a graph showing the tensile strength reduction rate of Examples 1-4 and Comparative Examples 1-3 of the present invention. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0029] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0030] Example 1

[0031] This embodiment proposes a composite rubber material for track rubber coating, including the following components in parts by weight: 50 parts of carbon black-doped modified boron nitride reinforcing filler, 25 parts of porous skeleton main filler, 10 parts of glutaric acid, 20 parts of natural rubber, 20 parts of styrene-butadiene rubber, 3 parts of benzothiazole disulfide, and 8 parts of zinc oxide.

[0032] The carbon black doped modified boron nitride reinforcing filler comprises the following components in parts by weight: 10 parts of modified boron nitride and 100 parts of carbon black.

[0033] The porous skeleton main filler comprises the following components in parts by weight: 20 parts of modified melamine skeleton material and 60 parts of multi-walled carbon nanotubes double-modified with stearic acid and chitosan.

[0034] The preparation method of carbon black doped modified boron nitride reinforcing filler specifically comprises the following steps:

[0035] (1) 10.0 g of boron nitride was added to 100 mL of a 30% sodium hydroxide solution, heated and stirred in an 80°C oil bath for 48 h, washed with distilled water until neutral, and then vacuum dried. Hydroxylation treatment can improve the dispersibility and stability of boron nitride in aqueous solution, and also provide reaction sites for boron nitride, making it easier to carry out functional modification. It can also improve the interfacial affinity of boron nitride in polymer composites, and better play the role of boron nitride in enhancing the hardness of rubber materials, improving wear resistance and improving anti-aging properties, thereby obtaining hydroxylated boron nitride;

[0036] (2) Add 2 mL of γ-glycidyloxypropyltrimethoxysilane to 100 mL of 90% ethanol solution, stir for 1 hour, then add the hydroxylated boron nitride described in step (1), heat in a water bath at 80°C for 1 hour, filter, wash the product with anhydrous ethanol for 5 times, and vacuum dry. γ-glycidyloxypropyltrimethoxysilane is used as a silane coupling agent to modify the filler, thereby improving the dispersibility of hydroxylated boron nitride in the rubber matrix and enhancing the interaction between the rubber matrix and the hydroxylated boron nitride, which plays a positive role in improving the various properties of the rubber material, thereby obtaining modified boron nitride;

[0037] (3) The modified boron nitride described in step (2) was added to 2L of deionized water, and ultrasonicated for 30 minutes to make it uniformly dispersed. Then, 100.0g of carbon black particles were added to the modified boron nitride dispersion. The carbon black type was BC2110, which has finer particles, larger specific surface area, better reinforcement, and better processing performance. High-pressure homogenization was first performed for 3 minutes, high-speed shearing was then performed for 10 minutes, and then ultrasonic treatment was performed for 50 minutes. Finally, high-pressure homogenization was performed for 60 minutes, and the product was filtered. The product was washed with deionized water 5 times and vacuum-treated. Air drying, through this process, the carbon black particles are adsorbed and doped on the modified boron nitride layer structure, which hinders the stacking of the boron nitride layer structure and further improves the compatibility with the rubber matrix. At the same time, the load-bearing effect of the modified boron nitride also improves the aggregation of carbon black particles, which is conducive to the carbon black to form a physical bond with the rubber molecules more fully, increase its hardness and strength, improve wear resistance, oxidation resistance and weather resistance, prevent aging and deterioration, effectively extend the service life of the rubber material, and obtain carbon black doped modified boron nitride reinforcing filler.

[0038] This embodiment provides a method for preparing a composite rubber material for track rubber coating, which specifically includes the following steps:

[0039] S1. Cut melamine into 4cm×4cm×0.5cm, wash it ultrasonically with 80% ethanol solution, dry it for later use, dissolve 0.5g tris(hydroxymethylaminomethane) in 250mL deionized water, and adjust the pH to 8.5 with hydrochloric acid solution, then put the pretreated melamine into tris(hydroxymethylaminomethane) buffer solution, add 0.5g dopamine, react at room temperature for 8h, collect the product after washing, melamine is a material similar to "elastic foam", its porous structure and high specific surface area characteristics, as a support structure of filler, give the rubber material excellent compression and cycle durability, can maintain stable performance under high pressure, and dopamine adheres to the melamine skeleton after polymerization, making the skeleton surface rough, which provides favorable conditions for building a more complex filler network, and obtains a modified melamine skeleton material;

[0040] S2, 1.0g chitosan was dissolved in 200mL dilute acetic acid solution, stirred for 12h, and set aside. 0.5g multi-walled carbon nanotubes were weighed and dispersed in 20mL deionized water, and ultrasonicated for 30min. The multi-walled carbon nanotubes were carboxylated multi-walled carbon nanotubes with a diameter of 20nm and a length of 12μm. They had high chemical activity, better mechanical properties and thermal stability, and were not easy to entangle and aggregate. They could significantly enhance the wear resistance, tear resistance and aging resistance of rubber materials, making them more durable in harsh environments. Then they were slowly added to the chitosan solution and condensed and refluxed. Under the conditions, the mixed solution was magnetically stirred at 98°C for 6 hours, cooled to room temperature, the pH of the solution was adjusted to 10.0 with dilute ammonia water, and then 2 mL of glutaraldehyde was added, and magnetically stirred at 60°C for 3 hours. The product was washed and centrifuged with dilute acetic acid and deionized water in turn, and freeze-dried. Glutaraldehyde was used as a cross-linking agent, and the surface deposition cross-linking method was used to adsorb and wrap chitosan on the surface of multi-walled carbon nanotubes, which was not only beneficial to the next modification treatment, but also could play the toughening effect of chitosan, so that the rubber material could better disperse the stress when subjected to external force, reduce the generation and expansion of cracks, and obtain chitosan-modified multi-walled carbon nanotubes;

[0041] S3, dispersing the chitosan modified multi-walled carbon nanotubes described in step S2 in 20 mL of deionized water, ultrasonicating for 30 min, dissolving stearic acid and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride in a mixture of 28 mL of acetone and 12 mL of anhydrous ethanol, wherein the amount of stearic acid added is 0.3 g, and the amount of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride added is 0.8 g, wherein stearic acid can not only promote the vulcanization reaction with zinc oxide, but also help to promote the uniform dispersion of fillers such as carbon black in the rubber matrix, thereby improving the rubber material. The uniformity and stability of the material were improved, and then added to the dispersion of multi-walled carbon nanotubes modified with chitosan, and magnetically stirred at 60°C for 24 hours. The product was washed and centrifuged with anhydrous ethanol and deionized water in turn, and vacuum dried. The surface of the multi-walled carbon nanotubes modified with chitosan was further grafted with stearic acid through a water-soluble coupling agent 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride. After chitosan deposition and stearic acid grafting, the dispersibility of the multi-walled carbon nanotubes was improved, and the tube wall structure became rough, which was conducive to the enhancement of adhesion ability, and the multi-walled carbon nanotubes double-modified with stearic acid and chitosan were obtained.

[0042] S4, dispersing the multi-walled carbon nanotubes double-modified with stearic acid and chitosan described in step S3 in 100 mL of deionized water, then soaking the modified melamine skeleton material described in step S1 therein, taking it out, vacuum drying, and then repeating this process 3 times, the multi-walled carbon nanotubes double-modified with stearic acid and chitosan can be attached to the skeleton structure of the modified melamine skeleton material, forming a three-dimensional network filler, reducing the aggregation and entanglement of the filler, and can be evenly dispersed in the rubber matrix, better improving the wear resistance, aging resistance and mechanical properties of the rubber material, and obtaining a porous skeleton main filler;

[0043] S5. Disperse the carbon black doped modified boron nitride reinforcing filler in 100 mL of deionized water, infiltrate the porous skeleton main filler described in step S4 therein, take it out, vacuum dry it, and repeat this process 3 times to obtain a filler compound system. The carbon black doped modified boron nitride reinforcing filler is attached to the structure of the porous skeleton main filler by vacuum infiltration, which can give full play to the synergistic effect of the main material and the supplementary material. The two form a unique network structure, which makes the filler network inside the rubber matrix more perfect, and significantly enhances the dispersibility and compatibility. Mix the natural rubber and styrene-butadiene rubber in an internal mixer for 2 minutes at a temperature of 135° C. and a speed of 80 rpm, and then add the filler compound system, glutaric acid, benzothiazole disulfide and zinc oxide, wherein glutaric acid can also increase the crosslinking density between materials, thereby enhancing the ability of the rubber macromolecular chains to resist deformation. Mix for 30 minutes, mix evenly, and thin it out. After standing for 8 hours, use a flat vulcanizer for compression molding to obtain a composite rubber material for track rubber coating.

[0044] In this embodiment, a scanning electron microscope is used to observe the microscopic morphology of the brittle fracture surface of the composite rubber material for track coating. Figure 1 This is a SEM image of the brittle fracture section of the composite rubber material for track rubber prepared in Example 1, magnified 400 times. Figure 1 The composite rubber material for track rubber coating prepared in this embodiment has a relatively complete three-dimensional network structure in its brittle fracture section and has good compatibility.

[0045] Example 2

[0046] This embodiment proposes a composite rubber material for track coating, comprising the following components in parts by weight: 40 parts of carbon black-doped modified boron nitride reinforcing filler, 20 parts of porous skeleton main filler, 8 parts of glutaric acid, 15 parts of natural rubber, 15 parts of styrene-butadiene rubber, 1 part of benzothiazole disulfide, and 5 parts of zinc oxide.

[0047] The carbon black doped modified boron nitride reinforcing filler comprises the following components in parts by weight: 8 parts of modified boron nitride and 50 parts of carbon black.

[0048] The porous skeleton main filler comprises the following components in parts by weight: 10 parts of modified melamine skeleton material and 40 parts of multi-walled carbon nanotubes double-modified with stearic acid and chitosan.

[0049] The preparation method of carbon black doped modified boron nitride reinforcing filler specifically comprises the following steps:

[0050] (1) 8.0 g of boron nitride was added to 100 mL of a 20% sodium hydroxide solution, heated and stirred in an oil bath at 70°C for 48 h, washed with distilled water until neutral, and then dried in a vacuum. Hydroxylation treatment can improve the dispersibility and stability of boron nitride in aqueous solution, provide reaction sites for boron nitride, make it easier to carry out functional modification, and improve the interfacial affinity of boron nitride in polymer composites, so as to better play the role of boron nitride in enhancing the hardness of rubber materials, improving wear resistance and improving anti-aging properties, thereby obtaining hydroxylated boron nitride;

[0051] (2) Add 1 mL of γ-glycidyloxypropyltrimethoxysilane to 100 mL of 90% ethanol solution, stir for 0.5 h, then add the hydroxylated boron nitride described in step (1), heat in a 70°C water bath for 1 h, filter, wash the product with anhydrous ethanol for 3 times, and vacuum dry. γ-glycidyloxypropyltrimethoxysilane is used as a silane coupling agent to modify the filler, thereby improving the dispersibility of hydroxylated boron nitride in the rubber matrix and enhancing the interaction between the rubber matrix and the hydroxylated boron nitride, which plays a positive role in improving the various properties of the rubber material, thereby obtaining modified boron nitride;

[0052] (3) The modified boron nitride described in step (2) is added to 2L of deionized water, and ultrasonicated for 10 minutes to make it uniformly dispersed. Then, 50.0g of carbon black particles are added to the modified boron nitride dispersion. The carbon black type is BC2110, which has finer particles, larger specific surface area, better reinforcement, and better processing performance. First, high-pressure homogenization is performed for 2 minutes, then high-speed shearing is performed for 5 minutes, and then ultrasonic treatment is performed for 30 minutes. Finally, high-pressure homogenization is performed for 50 minutes, and the product is filtered. The product is washed with deionized water for 3 times and vacuum dried. Through this process, the carbon black particles are adsorbed and doped on the modified boron nitride sheet structure, which hinders the stacking of the boron nitride sheet structure and further improves the compatibility with the rubber matrix. At the same time, the load-bearing effect of the modified boron nitride also improves the aggregation phenomenon of the carbon black particles, which is conducive to the carbon black to form a more complete physical combination with the rubber molecules, increase its hardness and strength, improve wear resistance, oxidation resistance and weather resistance, prevent aging and deterioration, and effectively extend the service life of the rubber material to obtain a carbon black doped modified boron nitride reinforcing filler.

[0053] This embodiment provides a method for preparing a composite rubber material for track rubber coating, which specifically includes the following steps:

[0054] S1. Cut melamine into 4cm×4cm×0.5cm, wash it ultrasonically with 80% ethanol solution, dry it for later use, dissolve 0.3g tris(hydroxymethylaminomethane) in 250mL deionized water, and adjust the pH to 8.5 with hydrochloric acid solution, then put the pretreated melamine into tris(hydroxymethylaminomethane) buffer solution, add 0.2g dopamine, react at room temperature for 6h, collect the product after washing, melamine is a material similar to "elastic foam", its porous structure and high specific surface area characteristics, as a support structure of filler, give the rubber material excellent compression and cycle durability, can maintain stable performance under high pressure, and dopamine adheres to the melamine skeleton after polymerization, making the skeleton surface rough, which provides favorable conditions for building a more complex filler network, and obtains a modified melamine skeleton material;

[0055] S2, 0.8g chitosan was dissolved in 200mL dilute acetic acid solution, stirred for 8h, and set aside. 0.2g multi-walled carbon nanotubes were weighed and dispersed in 20mL deionized water, and ultrasonicated for 20min. The multi-walled carbon nanotubes were carboxylated multi-walled carbon nanotubes with a diameter of 10nm and a length of 10μm. They had high chemical activity, better mechanical properties and thermal stability, and were not easy to entangle and aggregate. They could significantly enhance the wear resistance, tear resistance and aging resistance of rubber materials, making them more durable in harsh environments. Then they were slowly added to the chitosan solution and condensed under reflux conditions. The mixed solution was magnetically stirred at 90°C for 5h, cooled to room temperature, the pH of the solution was adjusted to 10.0 with dilute ammonia water, and then 1mL of glutaraldehyde was added, and magnetically stirred at 50°C for 2h. The product was washed and centrifuged with dilute acetic acid and deionized water in turn, and freeze-dried. Glutaraldehyde was used as a cross-linking agent, and the surface deposition cross-linking method was used to adsorb and wrap chitosan on the surface of multi-walled carbon nanotubes, which was not only beneficial to the next modification treatment, but also could play the toughening effect of chitosan, so that the rubber material could better disperse the stress when subjected to external force, reduce the generation and expansion of cracks, and obtain chitosan-modified multi-walled carbon nanotubes;

[0056] S3, dispersing the chitosan modified multi-walled carbon nanotubes described in step S2 in 20 mL of deionized water, ultrasonicating for 20 min, dissolving stearic acid and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride in a mixture of 28 mL of acetone and 12 mL of anhydrous ethanol, wherein the amount of stearic acid added is 0.2 g, and the amount of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride added is 0.6 g, wherein stearic acid can not only promote the vulcanization reaction with zinc oxide, but also help to promote the uniform dispersion of fillers such as carbon black in the rubber matrix, thereby improving the rubber material. The uniformity and stability of the material were improved, and then added to the dispersion of multi-walled carbon nanotubes modified with chitosan, and magnetically stirred at 50°C for 12 hours. The product was washed and centrifuged with anhydrous ethanol and deionized water in turn, and vacuum dried. The surface of the multi-walled carbon nanotubes modified with chitosan was further grafted with stearic acid through a water-soluble coupling agent 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride. After chitosan deposition and stearic acid grafting, the dispersibility of the multi-walled carbon nanotubes was improved, and the tube wall structure became rough, which was conducive to the enhancement of adhesion ability, and the multi-walled carbon nanotubes double-modified with stearic acid and chitosan were obtained.

[0057] S4, dispersing the multi-walled carbon nanotubes double-modified with stearic acid and chitosan described in step S3 in 100 mL of deionized water, then soaking the modified melamine skeleton material described in step S1 therein, taking it out, vacuum drying, and then repeating this process once, the multi-walled carbon nanotubes double-modified with stearic acid and chitosan can be attached to the skeleton structure of the modified melamine skeleton material, forming a three-dimensional network filler, reducing the aggregation and entanglement of the filler, and can be evenly dispersed in the rubber matrix, better improving the wear resistance, aging resistance and mechanical properties of the rubber material, and obtaining a porous skeleton main filler;

[0058] S5. Disperse the carbon black doped modified boron nitride reinforcing filler in 100 mL of deionized water, infiltrate the porous skeleton main filler described in step S4 therein, take it out, vacuum dry it, and repeat this process once to obtain a filler compound system. The carbon black doped modified boron nitride reinforcing filler is attached to the structure of the porous skeleton main filler by vacuum infiltration, which can give full play to the synergistic effect of the main material and the supplementary material. The two form a unique network structure, which makes the filler network inside the rubber matrix more perfect, and significantly enhances the dispersibility and compatibility. Mix the natural rubber and styrene-butadiene rubber in an internal mixer for 1 min at a temperature of 125° C. and a speed of 60 rpm, and then add the filler compound system, glutaric acid, benzothiazole disulfide and zinc oxide, wherein glutaric acid can also increase the crosslinking density between materials, thereby enhancing the ability of the rubber macromolecular chains to resist deformation. Mix for 20 min, mix evenly, and thin it out. After standing for 8 h, use a flat vulcanizer for compression molding to obtain a composite rubber material for track rubber coating.

[0059] Example 3

[0060] This embodiment proposes a composite rubber material for track rubber coating, comprising the following components in parts by weight: 45 parts of carbon black-doped modified boron nitride reinforcing filler, 22.5 parts of porous skeleton main filler, 9 parts of glutaric acid, 17.5 parts of natural rubber, 17.5 parts of styrene-butadiene rubber, 2 parts of benzothiazole disulfide, and 6.5 parts of zinc oxide.

[0061] The carbon black doped modified boron nitride reinforcing filler comprises the following components in parts by weight: 9 parts of modified boron nitride and 75 parts of carbon black.

[0062] The porous skeleton main filler comprises the following components in parts by weight: 15 parts of modified melamine skeleton material and 50 parts of multi-walled carbon nanotubes double-modified with stearic acid and chitosan.

[0063] The preparation method of carbon black doped modified boron nitride reinforcing filler specifically comprises the following steps:

[0064] (1) Add 9.0 g of boron nitride to 100 mL of 25% sodium hydroxide solution, heat and stir in a 75°C oil bath for 48 h, wash with distilled water until neutral, and then vacuum dry. Hydroxylation treatment can improve the dispersibility and stability of boron nitride in aqueous solution, provide reaction sites for boron nitride, make it easier to carry out functional modification, and improve the interfacial affinity of boron nitride in polymer composites, so as to better play the role of boron nitride in enhancing the hardness of rubber materials, improving wear resistance and improving anti-aging properties, thereby obtaining hydroxylated boron nitride;

[0065] (2) Add 1.5 mL of γ-glycidyloxypropyltrimethoxysilane to 100 mL of 90% ethanol solution, stir for 0.75 h, then add the hydroxylated boron nitride described in step (1), heat in a 75°C water bath for 1 h, filter, wash the product with anhydrous ethanol 4 times, and vacuum dry. γ-glycidyloxypropyltrimethoxysilane is used as a silane coupling agent to modify the filler, thereby improving the dispersibility of the hydroxylated boron nitride in the rubber matrix and enhancing the interaction between the rubber matrix and the hydroxylated boron nitride, which plays a positive role in improving the various properties of the rubber material, thereby obtaining a modified boron nitride.

[0066] (3) The modified boron nitride described in step (2) was added to 2L of deionized water, and ultrasonicated for 20 minutes to make it uniformly dispersed. Then, 75.0g of carbon black particles were added to the modified boron nitride dispersion. The carbon black type was BC2110, which has finer particles, larger specific surface area, better reinforcement, and better processing performance. The modified boron nitride dispersion was first homogenized at high pressure for 2.5 minutes, then sheared at high speed for 7.5 minutes, then ultrasonicated for 40 minutes, and finally homogenized at high pressure for 55 minutes. The product was filtered and washed with deionized water for 4 times. Vacuum drying, through this process, the carbon black particles are adsorbed and doped on the modified boron nitride layer structure, which hinders the stacking of the boron nitride layer structure and further improves the compatibility with the rubber matrix. At the same time, the load-bearing effect of the modified boron nitride also improves the aggregation of carbon black particles, which is conducive to the carbon black to form a more complete physical bond with the rubber molecules, increase its hardness and strength, improve wear resistance, oxidation resistance and weather resistance, prevent aging and deterioration, effectively extend the service life of the rubber material, and obtain carbon black doped modified boron nitride reinforcing filler.

[0067] This embodiment provides a method for preparing a composite rubber material for track rubber coating, which specifically includes the following steps:

[0068] S1. Cut melamine into 4cm×4cm×0.5cm, wash it ultrasonically with 80% ethanol solution, dry it for later use, dissolve 0.4g tris(hydroxymethylaminomethane) in 250mL deionized water, and adjust the pH to 8.5 with hydrochloric acid solution, then put the pretreated melamine into tris(hydroxymethylaminomethane) buffer solution, add 0.35g dopamine, react at room temperature for 7h, collect the product after washing, melamine is a material similar to "elastic foam", its porous structure and high specific surface area characteristics, as a support structure of filler, give the rubber material excellent compression and cycle durability, can maintain stable performance under high pressure, and dopamine adheres to the melamine skeleton after polymerization, making the skeleton surface rough, which provides favorable conditions for building a more complex filler network, and obtains a modified melamine skeleton material;

[0069] S2, dissolve 0.9g chitosan in 200mL dilute acetic acid solution, stir for 10h, standby, weigh 0.35g multi-walled carbon nanotubes and disperse them in 20mL deionized water, ultrasonicate for 25min, the multi-walled carbon nanotubes are carboxylated multi-walled carbon nanotubes, with a diameter of 15nm and a length of 11μm, which have high chemical activity, better mechanical properties and thermal stability, and are not easy to entangle and aggregate, and can significantly enhance the wear resistance, tear resistance and aging resistance of rubber materials, so that they show better durability in harsh environments, and then slowly add them to the chitosan solution, under condensation reflux conditions, The mixed solution was magnetically stirred at 94°C for 5.5 hours, cooled to room temperature, and the pH of the solution was adjusted to 10.0 with dilute ammonia water, followed by adding 1.5 mL of glutaraldehyde and magnetically stirred at 55°C for 2.5 hours. The product was washed and centrifuged with dilute acetic acid and deionized water in turn, freeze-dried, and glutaraldehyde was used as a cross-linking agent. The surface deposition cross-linking method was used to adsorb and wrap chitosan on the surface of multi-walled carbon nanotubes, which was not only conducive to the next modification treatment, but also could play the toughening effect of chitosan, so that the rubber material could better disperse stress when subjected to external force, reduce the generation and expansion of cracks, and obtain chitosan-modified multi-walled carbon nanotubes;

[0070] S3, dispersing the chitosan modified multi-walled carbon nanotubes described in step S2 in 20 mL of deionized water, ultrasonicating for 25 min, dissolving stearic acid and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride in a mixture of 28 mL of acetone and 12 mL of anhydrous ethanol, wherein the amount of stearic acid added is 0.25 g, and the amount of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride added is 0.7 g, wherein stearic acid can not only promote the vulcanization reaction with zinc oxide, but also help to promote the uniform dispersion of fillers such as carbon black in the rubber matrix, thereby improving the rubber The uniformity and stability of the material were then added to a dispersion of multi-walled carbon nanotubes modified with chitosan, and magnetically stirred at 55°C for 18 hours. The product was washed and centrifuged with anhydrous ethanol and deionized water in turn, and vacuum dried. The surface of the multi-walled carbon nanotubes modified with chitosan was further grafted with stearic acid through a water-soluble coupling agent 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride. After chitosan deposition and stearic acid grafting, the dispersibility of the multi-walled carbon nanotubes was improved, and the tube wall structure became rough, which was conducive to the enhancement of adhesion ability, and multi-walled carbon nanotubes double-modified with stearic acid and chitosan were obtained.

[0071] S4, dispersing the multi-walled carbon nanotubes double-modified with stearic acid and chitosan described in step S3 in 100 mL of deionized water, then soaking the modified melamine skeleton material described in step S1 therein, taking it out, vacuum drying, and then repeating this process twice, the multi-walled carbon nanotubes double-modified with stearic acid and chitosan can be attached to the skeleton structure of the modified melamine skeleton material, forming a three-dimensional network filler, reducing the aggregation and entanglement of the filler, and can be evenly dispersed in the rubber matrix, better improving the wear resistance, aging resistance and mechanical properties of the rubber material, and obtaining a porous skeleton main filler;

[0072] S5. Disperse the carbon black-doped modified boron nitride reinforcing filler in 100 mL of deionized water, and infiltrate the porous skeleton main filler described in step S4 therein, take it out, and vacuum dry it. Repeat this process twice to obtain a filler compound system. The carbon black-doped modified boron nitride reinforcing filler is attached to the structure of the porous skeleton main filler by vacuum infiltration, which can give full play to the synergistic effect of the main material and the supplementary material. The two form a unique network structure, which makes the filler network inside the rubber matrix more perfect, and significantly enhances the dispersibility and compatibility. Mix the natural rubber and styrene-butadiene rubber in an internal mixer for 1.5 min at a temperature of 130° C. and a speed of 70 rpm, and then add the filler compound system, glutaric acid, benzothiazole disulfide and zinc oxide, wherein glutaric acid can also increase the crosslinking density between materials, thereby enhancing the ability of the rubber macromolecular chains to resist deformation. Mix for 25 min, mix well, and then thin it out. After standing for 8 hours, use a flat vulcanizer for compression molding to obtain a composite rubber material for track rubber coating.

[0073] Example 4

[0074] This embodiment proposes a composite rubber material for track rubber coating, including the following components in parts by weight: 40 parts of carbon black-doped modified boron nitride reinforcing filler, 25 parts of porous skeleton main filler, 8 parts of glutaric acid, 20 parts of natural rubber, 20 parts of styrene-butadiene rubber, 3 parts of benzothiazole disulfide, and 8 parts of zinc oxide.

[0075] The carbon black doped modified boron nitride reinforcing filler comprises the following components in parts by weight: 10 parts of modified boron nitride and 50 parts of carbon black.

[0076] The porous skeleton main filler comprises the following components in parts by weight: 20 parts of modified melamine skeleton material and 60 parts of multi-walled carbon nanotubes double-modified with stearic acid and chitosan.

[0077] The preparation method of carbon black doped modified boron nitride reinforcing filler specifically comprises the following steps:

[0078] (1) 10.0 g of boron nitride was added to 100 mL of a 30% sodium hydroxide solution, heated and stirred in an 80°C oil bath for 48 h, washed with distilled water until neutral, and then vacuum dried. Hydroxylation treatment can improve the dispersibility and stability of boron nitride in aqueous solution, and also provide reaction sites for boron nitride, making it easier to carry out functional modification. It can also improve the interfacial affinity of boron nitride in polymer composites, and better play the role of boron nitride in enhancing the hardness of rubber materials, improving wear resistance and improving anti-aging properties, thereby obtaining hydroxylated boron nitride;

[0079] (2) Add 1 mL of γ-glycidyloxypropyltrimethoxysilane to 100 mL of 90% ethanol solution, stir for 0.5 h, then add the hydroxylated boron nitride described in step (1), heat in a water bath at 80° C. for 1 h, filter, wash the product with anhydrous ethanol 5 times, and vacuum dry. γ-glycidyloxypropyltrimethoxysilane is used as a silane coupling agent to modify the filler, thereby improving the dispersibility of the hydroxylated boron nitride in the rubber matrix and enhancing the interaction between the rubber matrix and the hydroxylated boron nitride, which plays a positive role in improving the various properties of the rubber material, thereby obtaining a modified boron nitride.

[0080] (3) The modified boron nitride described in step (2) is added to 2L of deionized water, and ultrasonicated for 10 minutes to make it uniformly dispersed. Then, 50.0g of carbon black particles are added to the modified boron nitride dispersion. The carbon black type is BC2110, which has finer particles, larger specific surface area, better reinforcement, and better processing performance. First, high-pressure homogenization is performed for 2 minutes, then high-speed shearing is performed for 5 minutes, and then ultrasonic treatment is performed for 30 minutes. Finally, high-pressure homogenization is performed for 50 minutes, and the product is filtered. The product is washed with deionized water for 5 times and vacuum dried. Through this process, the carbon black particles are adsorbed and doped on the modified boron nitride sheet structure, which hinders the stacking of the boron nitride sheet structure and further improves the compatibility with the rubber matrix. At the same time, the load-bearing effect of the modified boron nitride also improves the aggregation phenomenon of the carbon black particles, which is conducive to the carbon black to form a more complete physical combination with the rubber molecules, increase its hardness and strength, improve wear resistance, oxidation resistance and weather resistance, prevent aging and deterioration, and effectively extend the service life of the rubber material to obtain a carbon black doped modified boron nitride reinforcing filler.

[0081] This embodiment provides a method for preparing a composite rubber material for track rubber coating, which specifically includes the following steps:

[0082] S1. Cut melamine into 4cm×4cm×0.5cm, wash it ultrasonically with 80% ethanol solution, dry it for later use, dissolve 0.5g tris(hydroxymethylaminomethane) in 250mL deionized water, and adjust the pH to 8.5 with hydrochloric acid solution, then put the pretreated melamine into tris(hydroxymethylaminomethane) buffer solution, add 0.2g dopamine, react at room temperature for 6h, collect the product after washing, melamine is a material similar to "elastic foam", its porous structure and high specific surface area characteristics, as a support structure of filler, give the rubber material excellent compression and cycle durability, can maintain stable performance under high pressure, and dopamine adheres to the melamine skeleton after polymerization, making the skeleton surface rough, which provides favorable conditions for building a more complex filler network, and obtains a modified melamine skeleton material;

[0083] S2, 0.8g chitosan was dissolved in 200mL dilute acetic acid solution, stirred for 8h, and set aside. 0.5g multi-walled carbon nanotubes were weighed and dispersed in 20mL deionized water, and ultrasonicated for 20min. The multi-walled carbon nanotubes were carboxylated multi-walled carbon nanotubes with a diameter of 10nm and a length of 12μm. They had high chemical activity, better mechanical properties and thermal stability, and were not easy to entangle and aggregate. They could significantly enhance the wear resistance, tear resistance and aging resistance of rubber materials, making them more durable in harsh environments. Then they were slowly added to the chitosan solution and condensed under reflux conditions. The mixed solution was magnetically stirred at 98°C for 5h, cooled to room temperature, the pH of the solution was adjusted to 10.0 with dilute ammonia water, and then 2mL of glutaraldehyde was added, and magnetically stirred at 60°C for 2h. The product was washed and centrifuged with dilute acetic acid and deionized water in turn, and freeze-dried. Glutaraldehyde was used as a cross-linking agent, and the surface deposition cross-linking method was used to adsorb and wrap chitosan on the surface of multi-walled carbon nanotubes, which was not only conducive to the next modification treatment, but also could play the toughening effect of chitosan, so that the rubber material could better disperse the stress when subjected to external force, reduce the generation and expansion of cracks, and obtain chitosan-modified multi-walled carbon nanotubes;

[0084] S3, dispersing the chitosan modified multi-walled carbon nanotubes described in step S2 in 20 mL of deionized water, ultrasonicating for 20 min, dissolving stearic acid and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride in a mixture of 28 mL of acetone and 12 mL of anhydrous ethanol, wherein the amount of stearic acid added is 0.3 g, and the amount of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride added is 0.8 g, wherein stearic acid can not only promote the vulcanization reaction with zinc oxide, but also help to promote the uniform dispersion of fillers such as carbon black in the rubber matrix, thereby improving the rubber material. The uniformity and stability of the material were improved, and then added to the dispersion of multi-walled carbon nanotubes modified with chitosan, and magnetically stirred at 60°C for 12 hours. The product was washed and centrifuged with anhydrous ethanol and deionized water in turn, and vacuum dried. The surface of the multi-walled carbon nanotubes modified with chitosan was further grafted with stearic acid through a water-soluble coupling agent 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride. After chitosan deposition and stearic acid grafting, the dispersibility of the multi-walled carbon nanotubes was improved, and the tube wall structure became rough, which was conducive to the enhancement of adhesion ability, and the multi-walled carbon nanotubes double-modified with stearic acid and chitosan were obtained.

[0085] S4, dispersing the multi-walled carbon nanotubes double-modified with stearic acid and chitosan described in step S3 in 100 mL of deionized water, then soaking the modified melamine skeleton material described in step S1 therein, taking it out, vacuum drying, and then repeating this process 3 times, the multi-walled carbon nanotubes double-modified with stearic acid and chitosan can be attached to the skeleton structure of the modified melamine skeleton material, forming a three-dimensional network filler, reducing the aggregation and entanglement of the filler, and can be evenly dispersed in the rubber matrix, better improving the wear resistance, aging resistance and mechanical properties of the rubber material, and obtaining a porous skeleton main filler;

[0086] S5. Disperse the carbon black-doped modified boron nitride reinforcing filler in 100 mL of deionized water, infiltrate the porous skeleton main filler described in step S4 therein, take it out, vacuum dry it, and repeat this process once to obtain a filler compound system. The carbon black-doped modified boron nitride reinforcing filler is attached to the structure of the porous skeleton main filler by vacuum infiltration, which can give full play to the synergistic effect of the main material and the supplementary material. The two form a unique network structure, which makes the filler network inside the rubber matrix more perfect, and significantly enhances the dispersibility and compatibility. Mix the natural rubber and styrene-butadiene rubber in an internal mixer for 1 min at a temperature of 135° C. and a speed of 80 rpm, and then add the filler compound system, glutaric acid, benzothiazole disulfide and zinc oxide, wherein glutaric acid can also increase the crosslinking density between materials, thereby enhancing the ability of the rubber macromolecular chains to resist deformation. Mix for 20 min, mix evenly, and thin it out. After standing for 8 hours, use a flat vulcanizer for compression molding to obtain a composite rubber material for track rubber coating.

[0087] Comparative Example 1

[0088] This comparative example provides a composite rubber material for track coating, which differs from Example 1 in that the carbon black-doped modified boron nitride reinforcing filler does not contain modified boron nitride; the preparation method of the carbon black-doped modified boron nitride reinforcing filler does not include steps (1) and (2); and the preparation method of the composite rubber material for track coating is the same as that of Example 1.

[0089] Comparative Example 2

[0090] This comparative example provides a composite rubber material for track coating, which differs from Example 1 in that the porous skeleton main filler does not contain modified melamine skeleton material; the preparation method of carbon black doped modified boron nitride reinforcing filler is the same as that of Example 1; the preparation method of the composite rubber material for track coating does not include step S1.

[0091] Comparative Example 3

[0092] This comparative example provides a composite rubber material for track coating, which differs from Example 1 in that the porous skeleton main filler does not contain chitosan and stearic acid; the preparation method of the carbon black doped modified boron nitride reinforcing filler is the same as that of Example 1; the preparation method of the composite rubber material for track coating does not include steps S2 and S3.

[0093] Experimental Example 1

[0094] Mechanical properties test

[0095] Test samples: composite rubber materials for track coating prepared in Examples 1-4 and Comparative Examples 1-3.

[0096] Test method: Use a punching machine and a dumbbell-shaped cutter to cut the test sample into a standard specimen with a thickness of (2.0±0.2) mm and a gauge length of 20 mm. Under standard experimental conditions, place the standard specimen on a TCS-2000 tensile testing machine and set the moving speed of the clamp to 500 mm / min. Perform tensile strength and tear strength tests. Take the average of five data in each group as the test result. The tensile strength is tested in accordance with GB / T528-2009, and the tear strength is tested in accordance with GB / T529-2008.

[0097] Figure 2 The mechanical properties of Examples 1-4 and Comparative Examples 1-3 are shown in the figure. As shown in the figure, the tensile strength and tear strength of Examples 1-4 are 30.2-32.3MPa and 128-136KN·m -1 , indicating good mechanical properties; the tensile strength and tear strength of comparative examples 1-3 were 19.7-22.0MPa and 92-113KN·m -1 , indicating that the mechanical properties are poor; the carbon black-doped modified boron nitride reinforcing filler of Comparative Example 1 does not contain modified boron nitride, and the carbon black particles cannot adhere to the modified boron nitride carrier, which increases the aggregation of the particles, is not conducive to the improvement of the mechanical effect of carbon black, and cannot play the reinforcing effect of boron nitride on the rubber material, resulting in poor mechanical properties; the porous skeleton main filler of Comparative Example 2 does not contain modified melamine skeleton material, lacks a skeleton structure similar to "elastic foam", and other filler components cannot adhere, so that a uniform three-dimensional network structure of the filler cannot be formed to promote the transfer of stress, and is not conducive to the improvement of the tensile strength and tear strength of the rubber material by each component, resulting in poor mechanical properties; the porous skeleton main filler of Comparative Example 3 does not contain chitosan and stearic acid, and cannot modify the multi-walled carbon nanotubes, which is not conducive to the dispersibility and adhesion stability of the multi-walled carbon nanotubes, limits the enhancement of the mechanical properties of the rubber material, and results in poor mechanical properties.

[0098] Experimental Example 2

[0099] Wear resistance test

[0100] Test samples: composite rubber materials for track coating prepared in Examples 1-4 and Comparative Examples 1-3.

[0101] Test method: The dynamic wear resistance of the test sample was tested using a drum abrasion machine. The test process was carried out in accordance with GB / T9867-2008, where the roller speed was 40r / min, the lateral speed on the roller surface was 4.20mm / r, the sliding distance was 20m, and the load was 10N.

[0102] Figure 3 The wear results of Examples 1-4 and Comparative Examples 1-3 are shown in FIG. 1 . As shown in the figure, the wear of Examples 1-4 is 113.6-118.2 mm. 3 , indicating strong wear resistance; the wear amount of comparative examples 1-3 is 130.8-142.1mm 3 , indicating that the wear resistance is weak; the carbon black-doped modified boron nitride reinforcing filler of Comparative Example 1 does not contain modified boron nitride, and cannot adsorb the highly wear-resistant carbon black particles doped and evenly adhere to the structure of the porous skeleton main filler, which is not conducive to improving the dispersibility and compatibility of carbon black in the rubber matrix, and also limits the reinforcing effect of other components, and cannot effectively reduce the wear of the rubber material, resulting in weak wear resistance; the porous skeleton main filler of Comparative Example 2 does not contain modified melamine skeleton material, and the main framework structure is missing in the filler compound system, and a complete and uniform filler network cannot be formed, which limits the synergistic effect of other filler components on enhancing the wear resistance of rubber, resulting in weak wear resistance; the porous skeleton main filler of Comparative Example 3 does not contain chitosan and stearic acid, which increases the aggregation and entanglement of multi-walled carbon nanotubes, and is not conducive to the adhesion stability of multi-walled carbon nanotubes on the modified melamine skeleton material, which is not conducive to reducing the wear of the rubber material, resulting in weak wear resistance.

[0103] Experimental Example 3

[0104] Aging resistance test

[0105] Test samples: composite rubber materials for track coating prepared in Examples 1-4 and Comparative Examples 1-3.

[0106] Test method: Use a punching machine and a dumbbell-shaped cutter to cut the test sample into a standard specimen with a thickness of (2.0±0.2) mm and a gauge length of 20 mm. Then, the standard specimen is subjected to an aging test according to GB3512-2014. The aging temperature is 150°C and the time is 2 days. After the test, a tensile strength test is performed. Then, the data in Experimental Example 1 is used as the performance parameter before aging. The tensile strength decrease rate is calculated by the following formula. The greater the tensile strength decrease rate, the worse the aging resistance performance.

[0107] Tensile strength decrease rate (%) = (tensile strength before aging - tensile strength after aging) / tensile strength before aging × 100%

[0108] Figure 4 The tensile strength reduction rate results of Examples 1-4 and Comparative Examples 1-3 are shown in the figure; as shown in the figure, the tensile strength reduction rate of Examples 1-4 is 2.3-4.1%, indicating that the aging resistance is better; the tensile strength reduction rate of Comparative Examples 1-3 is 8.2-15.7%, indicating that the aging resistance is poor; the carbon black doped modified boron nitride reinforcing filler of Comparative Example 1 does not contain modified boron nitride, which can neither give full play to the good thermal conductivity of boron nitride to reduce rubber aging caused by overheating, nor is it conducive to the uniform dispersion of carbon black particles, which limits the absorption of ultraviolet rays and leads to poor aging. The porous skeleton main filler of Comparative Example 2 does not contain modified melamine skeleton material, which cannot promote the cross-linking reaction of rubber, weakens the network structure of rubber molecules, is not conducive to improving the aging resistance of rubber materials, and leads to poor aging resistance; the porous skeleton main filler of Comparative Example 3 does not contain chitosan and stearic acid, which is not conducive to reducing the aggregation and entanglement of multi-walled carbon nanotubes, and cannot be evenly dispersed in the modified melamine skeleton material and the rubber matrix, which is not conducive to effectively improving the aging resistance of rubber materials, and leads to poor aging resistance.

[0109] The above experimental results show that the mechanical properties, wear resistance and aging resistance of Examples 1-4 of the present invention are significantly better than those of the samples of Comparative Examples 1-3. Among them, Example 1 using carbon black doped modified boron nitride reinforcing filler and porous skeleton main filler has better tensile strength and tear strength, stronger wear resistance and better aging resistance. The carbon black doped modified boron nitride reinforcing filler is attached to the skeleton structure of the porous skeleton main filler to form a filler compound system, which can be evenly dispersed in the rubber matrix to form a more complete filler network. This network structure can enable the various components of the filler to better play a synergistic reinforcement role. Under the dual effects of structure and components, the wear resistance, aging resistance and mechanical properties of the rubber material are effectively enhanced.

[0110] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0111] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A composite rubber material for track rubber coating, characterized in that: The composite rubber material for track rubber coating comprises the following components in parts by weight: 40-50 parts of carbon black doped modified boron nitride reinforcing filler, 20-25 parts of porous skeleton main filler, 8-10 parts of glutaric acid, 15-20 parts of natural rubber, 15-20 parts of styrene-butadiene rubber, 1-3 parts of benzothiazole disulfide, and 5-8 parts of zinc oxide; the carbon black doped modified boron nitride reinforcing filler comprises the following components in parts by weight: 8-10 parts of modified boron nitride and 50-100 parts of carbon black; the porous skeleton main filler comprises the following components in parts by weight: 10-20 parts of modified melamine skeleton material and 40-60 parts of multi-walled carbon nanotubes double-modified with stearic acid and chitosan.

2. A method for preparing the composite rubber material for crawler track coating according to claim 1, characterized in that: The specific steps include: S1. Cut melamine into 4cm×4cm×0.5cm, wash with 80% ethanol solution by ultrasonic, dry for later use, dissolve 0.3-0.5g tris(hydroxymethylaminomethane) in 250mL deionized water, adjust pH to 8.5 with hydrochloric acid solution, put the pretreated melamine into tris(hydroxymethylaminomethane) buffer solution, add 0.2-0.5g dopamine, react at room temperature for 6-8h, collect the product after washing, and obtain modified melamine skeleton material; S2, dissolving 0.8-1.0g chitosan in 200mL dilute acetic acid solution, stirring for 8-12h, standby, weighing 0.2-0.5g multi-walled carbon nanotubes and dispersing them in 20mL deionized water, ultrasonicating for 20-30min, and then slowly adding them to the chitosan solution, under condensation reflux conditions, magnetically stirring the mixed solution at 90-98°C for 5-6h, cooling to room temperature, adjusting the pH of the solution to 10.0 with dilute ammonia water, then adding 1-2mL glutaraldehyde, magnetically stirring at 50-60°C for 2-3h, washing the product with dilute acetic acid and deionized water, centrifuging, and freeze-drying to obtain chitosan-modified multi-walled carbon nanotubes; S3, dispersing the chitosan-modified multi-walled carbon nanotubes described in step S2 in 20 mL of deionized water, ultrasonicating for 20-30 min, dissolving stearic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride in a mixture of 28 mL of acetone and 12 mL of anhydrous ethanol, and then adding the mixture to the chitosan-modified multi-walled carbon nanotube dispersion, stirring magnetically at 50-60° C. for 12-24 h, washing the product with anhydrous ethanol and deionized water in turn, centrifuging, and vacuum drying to obtain multi-walled carbon nanotubes dual-modified with stearic acid and chitosan; S4, dispersing the multi-walled carbon nanotubes double-modified with stearic acid and chitosan described in step S3 in 100 mL of deionized water, then soaking the modified melamine skeleton material described in step S1 therein, taking it out, vacuum drying, and then repeating this process 1-3 times to obtain a porous skeleton main filler; S5. Disperse the carbon black-doped modified boron nitride reinforcing filler in 100 mL of deionized water, and then infiltrate the porous skeleton main filler described in step S4 therein, take it out, and vacuum dry it. Repeat this process 1-3 times to obtain a filler compound system. Mix the natural rubber and styrene-butadiene rubber in an internal mixer for 1-2 min at a temperature of 125-135°C and a rotation speed of 60-80 rpm. Then add the filler compound system, glutaric acid, benzothiazole disulfide and zinc oxide, and mix for 20-30 min. After mixing evenly, thin it and take out the sheet. After standing for 8 hours, use a flat vulcanizer for compression molding to obtain a composite rubber material for track rubber coating.

3. The method for preparing the composite rubber material for crawler track coating according to claim 2, characterized in that: In step S2, the multi-walled carbon nanotubes are carboxylated multi-walled carbon nanotubes with a diameter of 10-20 nm and a length of 10-12 μm.

4. The method for preparing the composite rubber material for crawler track coating according to claim 3, characterized in that: In step S3, the amount of stearic acid added is 0.2-0.3 g, and the amount of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride added is 0.6-0.8 g.

5. The method for preparing the composite rubber material for crawler track coating according to claim 4, characterized in that: The preparation method of the carbon black doped modified boron nitride reinforcing filler specifically comprises the following steps: (1) Add 8.0-10.0 g of boron nitride to 100 mL of a 20-30% sodium hydroxide solution, heat and stir in an oil bath at 70-80 ° C for 48 h, wash with distilled water until neutral, and then vacuum dry to obtain hydroxylated boron nitride; (2) Add 1-2 mL of γ-glycidyloxypropyltrimethoxysilane to 100 mL of 90% ethanol solution, stir for 0.5-1 h, then add the hydroxylated boron nitride described in step (1), heat in a water bath at 70-80° C. for 1 h, filter, wash the product with anhydrous ethanol 3-5 times, and vacuum dry to obtain modified boron nitride; (3) Add the modified boron nitride described in step (2) to 2L of deionized water, and perform ultrasonic treatment for 10-30min to make it evenly dispersed. Then add 50.0-100.0g of carbon black particles to the modified boron nitride dispersion, first perform high-pressure homogenization for 2-3min, then perform high-speed shearing for 5-10min, and then perform ultrasonic treatment for 30-50min, and finally perform high-pressure homogenization for 50-60min, filter, wash the product with deionized water 3-5 times, and vacuum dry to obtain a carbon black-doped modified boron nitride reinforcing filler.

6. The method for preparing the composite rubber material for crawler track coating according to claim 5, characterized in that: In step (3), the carbon black type is BC2110.

Citation Information

Cited By

  • High-thermal-conductivity rubber as well as preparation method and application thereof

    CN120192665A

  • A kind of high thermal conductivity rubber and its preparation method and application

    CN120192665B